Subjective tinnitus patients with normal pure-tone hearing still suffer more informational masking in the noisy environment - Wang, Mengyuan; Liu, Jinjun; Kong, Lingzhi; Zhao, Yixin; Diao, Tongxiang; Ma, Xin (Frontiers in Neuroscience, 2022)
Subjective tinnitus patients experience more hearing difficulties than normal peers in complex hearing environments, even though most of these patients have normal pure-tone hearing thresholds. Using speech recognition tasks under different masking conditions can provide insight into whether the effects of tinnitus are lateralized and the mechanisms behind the effects. By simulating sound field recordings, we obtain a target speech sentence that can be perceived as presented on one side and noise or speech masking with or without spatial separation from it. Our study used the virtual sound field technique to investigate the difference in speech recognition ability between chronic subjective tinnitus patients and a normal-hearing control group under the four masking conditions (speech-spectrum noise masking or two-talker speech masking, with or without perceived spatial separation). Experiment 1 showed no differences for target speech perceived location (left or right), which rules out a lateralization of the effect of tinnitus patients. Experiment 2 further found that although tinnitus patients had weaker performance than normal people in very complex auditory scenarios, when the spatial cue of the target speech exists, they can make good use of this cue to make up for the original processing disadvantage and achieve a similar performance as the normal-hearing group. In addition, the current study distinguished the effects of informational masking and energetic masking on speech recognition in patients with tinnitus and normal hearing. The results suggest that the impact of tinnitus on speech recognition in patients is more likely to occur in the auditory center rather than the periphery.